Gambaran Kadar SGPT (Serum Glutamic Pyruvic Tansaminase Asam Amino) pada Pengguna SUPLEMEN - Hijral Aswad (Jurnal Media Laboran, 2017)
The background of this study is someone who frequently consume amino acid supplements on a regular basis with the aim to magnetize the muscles symmetrically and reduce body fat where the muscle can be large because the muscle fibers are trained so that size increases and muscle enlargement requires a lot of protein and carbohydrates to Weight training. The purpose of this study was to look at the levels of SGPT (Serum Glutamic Pyruvic Transaminase) in amino acid supplement users. The type of this research is laboratory observation with quantitative analysis technique. The samples examined were serum from amino acid supplement users at Banta'-bantaeng gym. The study was conducted on 9-10 July 2016 at the laboratory of Lung Health Center of Makassar Society. From the results of the study, the content of SGPT in Amino Acid Supplements users does not exceed the normal values ​​and can be expressed the levels of SGPT in normal amino acid supplement users, and to the supplement users to stay careful and careful in choosing the supplements to be consumed.